2015
DOI: 10.1177/1099800415569845
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Coping Style Affect Health Outcomes in Adults With Type 2 Diabetes

Abstract: This integrated model provides a holistic picture of how risk factors and coping style influence HrQoL and DSs in individuals with T2DM. Nurses could use active coping strategies in cognitive behavioral therapy to enhance glycemic control in patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
2
15
0
4
Order By: Relevance
“…As for age, elderly persons are at high risk for developing anxiety and depression . Lower education in our study was related to anxious temperament, it might be due to that people with lower education levels may not develop coping strategy for stressful events as compared with higher educated people . When looking at the hyperthymic and irritable temperaments, it was observed that female gender would significantly decrease these scores.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…As for age, elderly persons are at high risk for developing anxiety and depression . Lower education in our study was related to anxious temperament, it might be due to that people with lower education levels may not develop coping strategy for stressful events as compared with higher educated people . When looking at the hyperthymic and irritable temperaments, it was observed that female gender would significantly decrease these scores.…”
Section: Discussionmentioning
confidence: 53%
“…50 Lower education in our study was related to anxious temperament, it might be due to that people with lower education levels may not develop coping strategy for stressful events as compared with higher educated people. 51 When looking at the hyperthymic and irritable temperaments, it was observed that female gender would significantly decrease these scores. These two temperaments have been highly associated with the male gender, while females have higher scores on depressive, cyclothymic, and anxious temperaments.…”
Section: Discussionmentioning
confidence: 99%
“…This disease also has a high degree of health and financial burden 6 . It increases risk for cardiovascular diseases 7 and depression, resulting in low quality of life 8 . Proper lifestyle changes and adequate treatment are the keys to decelerate the occurrence of the complications 9 .…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that active coping has also been shown to benefit patients with non‐psychiatric disorders, including chronic illness (Stewart and Yuen ), HIV (Gore‐felton and Koopman ), diabetes (Huang et al . ), post‐stroke recovery (Tielemans et al . ), and cardiovascular disease (Chiavarino et al .…”
Section: Discussionmentioning
confidence: 99%
“…While active coping has been linked to better outcomes for patients with MDD (Southwick et al 2005;Bjørkløf et al 2013;Cairns et al 2014), it has also been reported to benefit many other psychiatric diseases, including Bipolar Disorder (Goossens et al 2008), Schizophrenia (Meyer 2001), Substance Abuse and Alcoholism (Moser and Annis 1996;Humphreys et al 1999), and Post-Traumatic Stress Disorder (PSTD) (Contractor et al 2016). It is notable that active coping has also been shown to benefit patients with non-psychiatric disorders, including chronic illness (Stewart and Yuen 2011), HIV (Gore-felton and Koopman 2008), diabetes (Huang et al 2016), post-stroke recovery (Tielemans et al 2014), and cardiovascular disease (Chiavarino et al 2012). By identifying HCN channel function in CA1 as a determinant of coping strategy, we reason that it could impact the course of disease in many chronic illnesses.…”
Section: Discussionmentioning
confidence: 99%